Nutrient dynamics during decomposition of four different pine litters - De Marco A.; Vittozzi P.; Rutigliano F.A.; Virzo de Santo A. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
The dynamics of N, K, Mg, Mn, Fe and Cu was investigated during litter decomposition, at Mount Vesuvius, of four different pine species (Pinus pinea L., P. laricio Poiret, P. sylvestris L., and P. nigra Arn.). Initial chemical composition of the brown needle litters differed among species. The data presented suggest that nutrient dynamics in studied litters is mainly regulated by the initial nutrient content. P. nigra, the litter richest in N, released the nutrient during decomposition; in contrast the other litters with a lower initial concentration accumulated N. K was accumulated in the late phase only by P. sylvestris that had the lowest initial K concentration. Mg was accumulated by all litters. Mn was accumulated in P. nigra and in P. pinea, the litters poorest in Mn, and released in P. sylvestris and P. laricio. Fe and Cu were accumulated in all litters independently of the initial concentration.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)